Nature Symbols and Symbolism in Sufic Poems of Ibn Arabi - Buana, Cahya (KARSA: Journal of Social and Islamic Culture, 2017)
Ibn Arabi is regarded as a pioneer of wahdat al-wujud concept seeing that all creatures unite with the essence of God. Ibn Arabi frequently depicts his concepts and thoughts on Sufism through poetries that contain nature symbols. It raises questions in this study: what symbols are in Ibn Arabi’s poetries? What do these symbols mean? Is there a correlation between nature symbols in his poetries with his concept of wahdat al-wujud? To answer those three questions, the author uses qualitative methodology by using a number of both primary and secondary resources for library research. To analyze the symbols, Arabic rhetoric science-based approach is used, especially bayan. The study finds that certain symbols have been used by Ibn Arabi as such sun, moon, star, earth and sky. Ibn Arabi uses the symbols of sun to represent God as the main source of universe, of moon to represent God’s tajalli in His creatures, of sky for the highest attribute of God, of earth for human’s contemptible nature, and of stars bridging the sky and earth representing spirit blown by God onto human. Hence, nature symbols themselves disprove the concept of wahdat al-wujud that has been proposed by scholars so far.Copyright (c) 2017 by KARSA. All right reserved DOI: 10.19105/karsa.v25i2.1304